Indirect joint petrophysical inversion of synthetic shallow-seismic and multi-offset ground-penetrating radar data. Issue 3 (31st January 2022) - Qin, Tan; Bohlen, Thomas; Pan, Yudi
SUMMARY: Both full-waveform inversion (FWI) of shallow-seismic and ground-penetrating radar (GPR) surface recordings have received particular attention in the past decade since they can reconstruct seismic and electromagnetic properties at high resolution. For consistent near-surface imaging, seismic and GPR wavefields can be combined by joint petrophysical inversion (JPI) using classical time-domain FWI. In conventional JPI of wavefields, both shallow-seismic and multi-offset GPR data contribute to reconstructing the same petrophysical parameters. In this paper, we show that seismic and GPR wavefields have different sensitivities to these parameters assuming the widely established petrophysical model combining the Gassmann fluid substitution model, the complex refractive index model and Archie's equation. Based on this observation, we propose a new coupling strategy of petrophysical parameters which we call indirect JPI. In indirect JPI, seismic data is primarily used for porosity reconstruction, while GPR data is used only for saturation reconstruction. Unlike conventional JPI, we first update the seismic and GPR parameters using non-petrophysical parametrizations and then transform the most reliable estimates to petrophysical parameters. 2-D synthetic tests show that indirect JPI can provide more accurate and consistent results than conventional JPI. In addition, indirect JPI is more robust when uncertainties exist in petrophysical a priori knowledge. More importantly, indirect JPI has the flexibility to integrate different types of seismic and electromagnetic waves and acquisition geometries depending on the target of interest, resulting in the best solution. Indirect JPI has been proven to be a promising approach for multiparameter reconstructions (seven parameters in this study).